Quality Of Physical Education Questions For Grade Vi Of State Elementary School 84 In Bengkulu City - Setiawan, Ilham Bagus; Dewi, Citra; Perdima, Feby Elra (Journal of Physical Education and Sports, 2026)
This study aims to determine the quality of Physical Education (PJOK) test items for grade VI of SD Negeri 84 in Bengkulu City in terms of difficulty level, discriminating power, and distractor level. This type of research is quantitative descriptive research, descriptive research attempts to provide systematically and accurately the actual facts and characteristics of a particular population. This research was conducted by collecting several data including exam questions, answer keys, and student answer sheets which were then processed and analyzed so that information can be obtained regarding the quality of multiple-choice test items for the semester exam on the subject of PJOK in SD Negeri 84 Bengkulu City grade VI. The sample in this study was 20 students. The results of the study showed that the quality of the semester exam questions for the subject of Physical Education in Elementary School 84 Bengkulu City, which was reviewed from the level of difficulty, discriminating power and distractor level, obtained a difficulty index p < 0.3 of 3 with a percentage of 15%, then a difficulty index of 0.3 - 0.7 of 6 with a percentage of 30% and then a difficulty index P > 0.7 of 11 with a percentage of 55%. Discrimination Level Criteria Items with poor classification were 1 with a percentage of 3%, moderate classifications were 3 with a percentage of 8%, good classifications were 3 with a percentage of 8%, very good classifications were 33 with a percentage of 83% and very poor classifications were 0 with a percentage of 0%. The criteria for assessing the effectiveness of distractors with very good classifications are 11 with a percentage of 28%, good classifications are 1 with a percentage of 3%, quite good classifications are 0 with a percentage of 0%, less good classifications are 2 with a percentage of 5% and bad classifications are 28 with a percentage of 65%.